(untitled) (Scientia Agricola, 2021)
Land use and tillage practices may change soil structure and undermine sustainable agriculture; however, such changes are hardly identified in the short term. In this sense, agroforestry systems have been used to reduce soil degradation and promote sustainable production in coffee plantations. These areas are expected to have well-structured soils and hence improved root distribution. This study aimed to evaluate soil quality by the morphostructural and root distribution analyses comparing open-grown coffee and coffee in agroforestry systems with rubber trees for 19 years, in an Oxisol in northern Paraná State (Brazil). Treatments consisted of open-grown coffee (OG), coffee partially shaded by rubber trees (PSH), and coffee fully shaded by rubber trees (FSH). The mapping of morphostructural features and soil resistance to penetration in “cultural profile” walls identified changes in soil structure resulting from different tillage systems. Root distribution was better in coffee plants grown in PSH and FSH systems. At greater depths, cultural profiles of FSH and PSH showed a larger numbers of roots compared to OG. Among the three systems, PSH provided a better environment for root growth and distribution. This result could be attributed to the high biological activity and interaction between roots and aggregates in that profile. The FSH agroforestry system provided less compact morphological structures and more roots throughout the soil profile. The agroforestry systems presented fewer soil structural changes by tillage operations and lower values of soil penetration resistance. Coffee root distribution was an effective indicator of soil quality and consistent with the morphostructural characterization of cultural profile.